Adaptive Acculturation in Context: Batak Students and the Reconfiguration of Social Integration in Eastern Indonesia - Salni Rosita Silaban; Tonny Donald Pariela; Dominggus E.B. Saija (Baileo: Jurnal Sosial Humaniora, 2026)
This study examines the social adaptation of Batak students in Rumah Tiga, Ambon, and reconstructs the concept of social integration within the context of Indonesia’s island societies. It responds to the dominance of deficit-oriented approaches in migrant adaptation studies, which overemphasize conflict, culture shock, and marginalization, by proposing an alternative perspective: adaptive acculturation in context. This perspective conceptualizes adaptation as a contextual, relational, and value-based process mediated through everyday social interactions and cultural resonance. A qualitative descriptive-interpretive design was employed. Data were collected through participant observation, semi-structured in-depth interviews with 11 purposively selected informants, and document analysis. The data were analyzed using an interactive model involving data reduction, data display, and conclusion drawing. The findings reveal that social adaptation occurs relatively rapidly and positively through value negotiation, participation in informal social spaces, and the transformation of interpersonal relations from functional interactions into kinship-like ties. Initial barriers, including linguistic differences and cultural perceptions, are gradually overcome through informal learning and active engagement in local social life. Adaptation is facilitated by the interplay of bonding and bridging social capital, as well as shared cultural values such as kinship and mutual cooperation. This study contributes by introducing cultural resonance as a key mechanism of cross-cultural adaptation, highlighting informal spaces as micro-sites of integration, and reconceptualizing social integration as a dynamic and co-constructed process.